Faktor-faktor yang mempengaruhi motivasi pelajar sekolah menengah terhadap pembelajaran sains dan matematik - Azlina, Tamby Ahmad. (Universiti Malaysia Sarawak (UNIMAS), 2003)
The aim ofthis study is to determine the motivation ofstudents towards learning of sciene and mathematic in SMK Tabuan Jaya and related factors (learning · environments, families support, learning culture and learning styles). It also determines the difference among students of various demographic characteristic (gender, race, parents income, number of children, and parents educational qualification) in terms of their motivation toward learning of sciene and mathematic. A survey methodology was used in this study. The populations of this study were all students in form four and form jive of the schools. A stratified sampling technique was used to obtain a sample ofso students for this study. The findings of the study showed that SI.25 % of the students had a high motivation toward learning of science and mathematic and IS.75 % had a moderate motivation. Also, there is no significant difference among student of various demographic characteristic (gender, race, parents income, number ofchildren and parents educational qualification) in term of their motivation toward of learning sciene and mathematic. The study also revealed that there was correlation between learning environment, family's support, learning culture and learning style with motivation of students towards learning of science and mathematic. The implication of this study in that schools need to improve their effort in providing better learning environment, enhance relationship with parents and develop better learning culture, which will help to increase motivation among student toward learning ofsciene and mathematic. Also, this study can be used as a guideline by future researcher to study students' motivation in learning.